Influência de dieta a base de leite de cabra com teor aumentado de ácido linoléico conjugado (CLA) sobre o peso corporal, parâmetros bioquímicos e aspectos histopatológicos de ratos - Rodrigues, Raphaela Araújo Veloso (2012)
Goat milk is a high nutritional value food with an important economic potential. Its nutritional characteristics reveal some advantages over cow milk, as better digestibility and lower allergic potential. Among the compounds with potential benefit to human health present in goat milk, we can cite the conjugated linoleic acid (CLA). This fatty acid is found especially in dairy and meat products derived from ruminants. CLA has shown biological activities as reduction of fat and body weight, maintaining or increasing lean body mass, protection of cardiovascular function, improvement of insulin sensitivity and increase of calcium retention. With the great attention given to the compound, researchers have been developing methods to increase the amount of CLA in milk of ruminants. This study aimed to evaluate the effectiveness of a goat milk manipulated to have a greater amount of CLA in male Wistar rats. A total of 36 animals was divided into three groups, treated during ten weeks with a diet based on AIN-93, each group with different fat sources, was formed: soybean oil (control group - CON), coconut oil (CO) or goat milk fat with high content of CLA (CLArich). Weight and food intake were recorded weekly. At the end of this period, the animals were anesthetized and then sacrificed. Blood samples were collected and liver and intestine removed for histopathological evaluation. The weight had no significant difference among the three groups at the beginning or end of the experiment. However, CLA-rich group had higher weights from the second to the fifth weeks of the experiment, compared to the others groups. Groups CO and CLA-rich groups showed a trend to a higher feed intake, but not during all weeks. In the CLA-rich group was observed a reduction of serum triglycerides (TG) and TG / HDL ratio and increases of HDL and total cholesterol (TC). The serum glucose of CLA-rich group did not differed from the CON group, but was significantly higher compared to CO. Pathological changes were not found in the intestine, while livers of animals of all three groups showed hepatic steatosis. Such results show a possible beneficial effect of goat milk with high content of CLA on lipid profile in rats, with no significant change of serum glucose, suggesting a functional action to this food. However, further studies are needed.